Tau protein squired by molecular chaperones during alzheimer's disease - Gorantla, Nalini Vijay; Chinnathambi, Subashchandrabose (Journal of Molecular Neuroscience, 2018)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive neuronal loss, caused by misfolding and accumulation of tau and Amyloid -42. Cellular mechanisms involving phosphatases, chaperones, ubiquitin proteasome system (UPS) and aggresomes solubilize or remove these toxic aggregates. Chaperones such as Hsp70 and Hsp90 functions in folding tau to its native form or in the downstream degrade and eliminated tau from the cell. Chaperones are involved in lysosomal degradation of tau by a process called chaperone mediated autophagy (CMA). In pathological conditions, chaperones fail to remove the toxic tau species, leading to their accumulation. In this scenario, inhibiting the chaperone activity would aid in overcoming AD. Small molecules inhibitors against chaperone activity are known to be effective in the clearance of aberrant tau from cell. In this review, the aspects of inhibition and prevention of tau aggregates formation are discussed in terms of chaperone activity and their small molecule modulators.

Molecular cobalt(II) complexes for tau polymerization in Alzheimer's disease - Gorantla, Nalini Vijay; Landge, Vinod G.; Nagaraju, Pramod Gudigenahally; Priyadarshini, Poornima C. G.; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (ACS Omega, 2019)
Tau is an axonal protein known to form abnormal aggregates and is the biomarker of Alzheimer's disease. Metal-based therapeutics for inhibition of Tau aggregation is limited and rarely reported in contemporary science. Here, we report the first example of rationally designed molecular cobalt(II)-complexes for effective inhibition of Tau and disaggregation of preformed Tau fibrils. The mechanistic studies reveal that prevention of Tau aggregation by cobalt-based metal complexes (CBMCs) is concentration-dependent and Tau seldom exhibits conformational changes. Interestingly, CBMCs play dual role in causing disassembly of preformed aggregates as well as inhibition of complete Tau aggregation. Furthermore, CBMCs were nontoxic and maintained the tubulin network intact. CBMCs also prevented okadaic acid-induced toxicity in SH-SY5Y cells thus, preventing hyperphosphorylation of Tau. We believe that this unprecedented finding by the newly developed molecular complexes has a potential toward metal-based therapeutics for Alzheimer's disease.

Autophagic pathways to clear the tau aggregates in alzheimer's disease - Gorantla, Nalini Vijay; Chinnathambi, Subashchandrabose (Cellular and Molecular Neurobiology, 2020)
Tau is a microtubule-associated protein with an intrinsically unstructured conformation. Tau is subjected to several pathological post-translational modifications (PTMs), leading to its loss of interaction with microtubules and accumulation as neurofibrillary tangles (NFTs) in neurons. Tau aggregates impede functions of endoplasmic reticulum and mitochondria leading to the generation of oxidative stress and in turn amplifying the Tau aggregation. Tau is channelled to chaperones for folding into their native form, which otherwise causes its degradation and clearance. Cellular response triggers the activation of ubiquitin-proteasome system or autophagy to facilitate Tau degradation, based on the PTMs or mutations associated with Tau. Further, autophagy can be selective where Hsc70 interacts with Tau in monomeric, oligomeric and aggregated form and drives its clearance by chaperone-mediated autophagy pathway (CMA). Lysosome-associated membrane proteins-2A (LAMP-2A) is the key player of CMA that recognises Hsc70-Tau complex and triggers the downstream cascade. Thus, it becomes challenging for mutant Tau to be cleared by CMA as it loses its affinity for Hsc70 and LAMP-2A. In such a scenario, Tau might be degraded by macroautophagy otherwise sequestered by aggresomes. Henceforth, the degradation of Tau and its blockage that is associated with various PTMs of Tau would explain the dynamics of Tau degradation or accumulation in AD. Further, unveiling the role of accessory proteins involved in these degradation pathways would help in understanding their loss of function and preventing Tau clearance.
Keywords: Alzheimer's disease; Chaperone-mediated autophagy; Lysosome-associated membrane proteins-2A; Macroautophagy; Neurofibrillary tangles; Tau; Tau degradation; Ubiquitin-proteasome system

Basic limonoid modulates chaperone-mediated proteostasis and dissolve Tau fibrils - Gorantla, Nalini Vijay; Das, Rashmi; Chidambaram, Hariharakrishnan; Dubey, Tushar; Mulani, Fayaj A.; Thulasiram, V. Hirekodathakallu; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
The Alzheimer's disease pathology is associated with accumulation of intracellular neurofibrillary tangles and extracellular senile plaques. The formation of initial nucleus triggers conformational changes in Tau and leads to its deposition. Hence, there is a need to eliminate these toxic proteins for proper functioning of neuronal cells. In this aspect, we screened the effect of basic limonoids such as gedunin, epoxyazadiradione, azadirone and azadiradione on inhibiting Tau aggregation as well as disintegration of induced Tau aggregates. It was observed that these basic limonoids effectively prevented aggregates formation by Tau and also exhibited the property of destabilizing matured Tau aggregates. The molecular docking analysis suggests that the basic limonoids interact with hexapeptide regions of aggregated Tau. Although these limonoids caused the conformational changes in Tau to beta-sheet structure, the cytological studies indicate that basic limonoids rescued cell death. The dual role of limonoids in Tau aggregation inhibition and disintegration of matured aggregates suggests them to be potent molecules in overcoming Tau pathology. Further, their origin from a medicinally important plant neem, which known to possess remarkable biological activities was also found to play protective role in HEK293T cells. Basic limonoids were non-toxic to HEK293T cells and also aided in activation of HSF1 by inducing its accumulation in nucleus. Western blotting and immunofluorescence studies showed that HSF1 in downstream increased the transcription of Hsp70 thus, aggravating cytosolic Hsp70 levels that can channel clearance of aberrant Tau. All these results mark basic limonoids as potential therapeutic natural products.

EGCG impedes human Tau aggregation and interacts with Tau - Sonawane, Shweta Kishor; Chidambaram, Hariharakrishnan; Boral, Debjyoti; Gorantla, Nalini Vijay; Balmik, Abhishek Ankur; Dangi, Abha; Ramasamy, Sureshkumar; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
Tau aggregation and accumulation is a key event in the pathogenesis of Alzheimer's disease. Inhibition of Tau aggregation is therefore a potential therapeutic strategy to ameliorate the disease. Phytochemicals are being highlighted as potential aggregation inhibitors. Epigallocatechin-3-gallate (EGCG) is an active phytochemical of green tea that has shown its potency against various diseases including aggregation inhibition of repeat Tau. The potency of EGCG in altering the PHF assembly of full-length human Tau has not been fully explored. By various biophysical and biochemical analyses like ThS fluorescence assay, MALDI-TOF analysis and Isothermal Titration Calorimetry, we demonstrate dual effect of EGCG on aggregation inhibition and disassembly of full-length Tau and their binding affinity. The IC50 for Tau aggregation by EGCG was found to be 64.2 mu M.

Melatonin interacts with repeat domain of Tau to mediate disaggregation of paired helical filaments - Balmik, Abhishek Ankur; Das, Rashmi; Dangi, Abha; Gorantla, Nalini Vijay; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Biochimica Et Biophysica Acta-General Subjects, 2020)
Tau is the major neuronal protein involved in the stabilization of microtubule assembly. In Alzheimer's disease, Tau self-assembles to form intracellular protein aggregates which are toxic to cells. Various methods have been tried and tested to restrain the aggregation of Tau. Most of the agents tested for this purpose have limitations in their effectiveness and availability to neuronal cells. We have tested melatonin, a neurohormone secreted by pineal gland and a well-known anti-oxidant, for its ability to interact with the repeat domain of Tau using ITC and NMR. In aggregation inhibition and disaggregation studies of repeat Tau, melatonin was found to modulate the aggregation propensity of repeat Tau at a concentration of 5000 mu M and was more effective in dissolving preformed aggregates rather than acting as an aggregation inhibitor. However, there were no major conformational changes in Tau in presence of melatonin as observed by CD spectroscopy. On the basis of our findings, we are proposing a mechanism by which melatonin can interact with the repeat domain of Tau and exhibit its disaggregation effect.
Keywords: Alzheimer's disease; Disaggregation; melatonin; Paired helical filaments; tau protein; Tauopathies

Photodynamic exposure of Rose-Bengal inhibits Tau aggregation and modulates cytoskeletal network in neuronal cells - Dubey, Tushar; Gorantla, Nalini Vijay; Chandrashekara, Kagepura Thammaiah; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
The intracellular Tau aggregates are known to be associated with Alzheimer's disease. The inhibition of Tau aggregation is an important strategy for screening of therapeutic molecules in Alzheimer's disease. Several classes of dyes possess a unique property of photo-excitation, which is applied as a therapeutic measure against numerous neurological dysfunctions. Rose Bengal is a Xanthene dye, which has been widely used as a photosensitizer in photodynamic therapy. The aim of this work was to study the protective role of Rose Bengal against Tau aggregation and cytoskeleton modulations. The aggregation inhibition and disaggregation potency of Rose Bengal and photo-excited Rose Bengal were observed by in-vitro fluorescence, circular dichroism, and electron microscopy. Rose Bengal and photo-excited Rose Bengal induce minimal cytotoxicity in neuronal cells. In our studies, we observed that Rose Bengal and photo-excited Rose Bengal modulate the cytoskeleton network of actin and tubulin. The immunofluorescence studies showed the increased filopodia structures after photo-excited Rose Bengal treatment. Furthermore, Rose Bengal treatment increases the connections between the cells. Rose Bengal and photo-excited Rose Bengal treatment-induced actin-rich podosome-like structures associated with cell membranes. The in-vivo studies on UAS E-14 Tau mutant Drosophila suggested that exposure to Rose Bengal and photo-excited Rose Bengal efficiency rescues the behavioural and memory deficit in flies. Thus, the overall results suggest that Rose Bengal could have a therapeutic potency against Tau aggregation.

Residue-based propensity of aggregation in the Tau amyloidogenic hexapeptides AcPHF6*and AcPHF6 - Dangi, Abha; Balmik, Abhishek Ankur; Ghorpade, Archana Kisan; Gorantla, Nalini Vijay; Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose; Marelli, Udaya Kiran (RSC Advances, 2020)
In Alzheimer's disease and related tauopathies, the aggregation of microtubule-associated protein, Tau, into fibrils occursviathe interaction of two hexapeptide motifs PHF*(275)VQIINK(280)and PHF(306)VQIVYK(311)as beta-sheets. To understand the role of the constituent amino acids of PHF and PHF* in the aggregation, a set of 12 alanine mutant peptides was synthesized by replacing each amino acid in PHF and PHF* with alanine and they were characterized by nuclear magnetic resonance (NMR) spectroscopy, circular dichroism (CD), transmission electron microscopy (TEM) and ThS/ANS fluorescence assay. Our studies show that while the aggregation was suppressed in most of the alanine mutant peptides, replacement of glutamine by alanine in both PHF and PHF* enhanced the fibrillization.

Transition metal nickel prevents Tau aggregation in Alzheimer's disease - Gorantla, Nalini Vijay; Das, Rashmi; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Alzheimer's disease is the leading cause of dementia, effecting majority of aged people worldwide. The multifaceted effectors of Alzheimer's disease primarily include Tau, amyloid-beta along with hyper activation of kinases, oxidative stress and mutations etc., makes it challenging to design therapeutics. Tau is a microtubule-associating protein, which is subjected to cellular stress resulting in the formation of neurofibrillary tangles, leading to loss of affinity for microtubules. This causes loss of microtubule stability and in turn alters axonal integrity. In the present work, emphasis towards understanding interaction of nickel with Tau was made. Metals such as iron, zinc, copper and lead etc., are known to modulate Tau conformation and enhance its aggregation. Our results showed the deliverance of Tau aggregation by nickel and its synthetic morpholine conjugate. Nickel prevents aggregation by inducing degradation of Tau as evidenced by SDS-PAGE and TEM. Nickel and the synthetic conjugate being non toxic to neuro2a cells and prevent Tau aggregation, might direct these complexes to overcome AD. (C) 2019 Published by Elsevier B.V.
Keywords: Aggregation; Alzheimer's disease; metals; Morpholine; Nickel chloride; Tau

Implications of valosin-containing protein in promoting autophagy to prevent tau aggregation - Chinnathambi, Subashchandrabose; Gorantla, Nalini Vijay (Neuroscience, 2021)
and cellular degradative mechanisms modulate Tau aggregation. During aging and neu-rodegenerative disorders, the cellular proteostasis is disturbed due to impaired protective mechanisms. This results in accumulation of aberrant Tau aggregates in the neuron that leads to microtubule destabilization and neuronal degeneration. The intricate mechanisms to prevent Tau aggregation involve chaperones, autophagy, and proteasomal system have gained main focus about concerning to therapeutic intervention. However, the thor-ough understanding of other key proteins, such as Valosin-containing protein (VCP), is limited. In various neu-rodegenerative diseases, the chaperone-like activity of VCP is involved in preventing protein aggregation and mediating the degradation of aberrant proteins by proteasome and autophagy. In the case of Tau aggregation associated with Alzheimer's disease, the importance of VCP is poorly understood. VCP is known to co-localize with Tau, and alterations in VCP cause aberrant accumulation of Tau. Nevertheless, the direct mechanism of VCP in altering Tau aggregation is not known. Hence, we speculate that VCP might be one of the key modulators in preventing Tau aggregation and can disintegrate Tau aggregates by directing its clearance by autophagy. = 2021 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: Autophagy; segregase; Tau aggregates; Ubiquitin-proteasome system; valosin-containing protein